Inventory investment and production in Europe: Is there a pattern? - Yngve Abrahamsen; Jochen Hartwig (ETH Zurich, KOF Swiss Economic Institute, 2011)
The paper investigates the nexus between inventory investment and the change in aggregate production for 29 European countries over the period 2000-2009. A special interest is taken in the Great Recession of 2008/09. For most countries, a fairly uniform pattern emerges. Inventory investment is positively correlated with changes in production and follows the latter with a time-lag of two to three quarters. Therefore, there is no evidence that inventory investment either drives or smoothes the business cycle. Very few countries - Austria, Greece, Spain, and Switzerland - diverge from the typical pattern. This might hint to problems with respect to data quality.
Keywords: E22; E32; O52; 330; Inventory investment; production; business cycle; Great Recession in Europe; Lagerinvestition; Gesamtwirtschaftliche Produktion; Europa